Is Human Capital a Major Determinant of the FDI Inflows? Empirical Evidences from the EU States - Laura Diaconu (CES Working Papers, 2016)
Knowing the importance of foreign direct investments (FDI) for economic development of a country, the main objective of the present paper is to analyse whether the human capital represents a major determinant for the multinational companies to invest in the European Union states. Moreover, we intend to discover if there are some other factors that may enhance this role played by human capital. In order to reach the established objective, we have investigated the literature, including several case studies, and we have statistically analysed the secondary data offered by various yearbooks and reports. The relevance of this paper results from the fact that the conclusions may offer valuable information for the policy makers to create a more favourable environment for the FDI inflows in the EU states, on long term.
Keywords: F21; F23; J24; 330; FDI inflows; human capital; EU states